Comparison of Scientific Publications from Three Different Clinical Disciplines of German Universities - Schwarzer, Michael; Alscher, Leonhard; Doenst, Torsten (The Thoracic and Cardiovascular Surgeon, 2019)
Background Scientific publications are important for the advancement in medicine. Surgical disciplines including cardiac surgery are frequently considered not scientifically leading. However, a specific comparison between surgical and nonsurgical disciplines has not yet been performed. We thus compared scientific output of German departments of cardiac surgery with nonsurgical cardiology departments and surgical departments not addressing the heart (general surgery) of 34 universities in Germany.Methods For each university, the personnel working at the different departments were identified on the internet homepage in 2014. We searched for publications of these persons in 2011 to 2013 on PubMed, identified author position, coauthors, and type of article, as well as journal impact factor (JIF).Results There were 931 academic persons in cardiac surgery, 1,486 in general surgery, and 1,814 in cardiology with 12,096 publications related to these persons on PubMed. Cardiology published most manuscripts, including manuscripts from research conducted (first author), initiated (senior author), or both. Cardiac surgery had the least publications and had fewer authors from other departments or institutions. The average JIF was higher in cardiology compared with the two surgical disciplines. However, relating the number of publications to the number of employees in the departments, the differences were no longer apparent.Conclusion We conclude that the number of publications in German universities appears to be a function of the number of academic personnel and not of the discipline. The lower JIFs in surgery may be due to the smaller surgical fields and/or due to less high impact interdisciplinary/interinstitutional publications in surgery.
Keywords: scientific output; university; research